Mondrian Math: An Artful Exploration of Area and Perimeter - Johnston, Elisabeth; Ward, Elizabeth Kennedy (Ohio Journal of School Mathematics, 2018)
Playing games in the math classroom is an excellent way for students to develop fluency and practice skills. This paper explains Mondrian Math, a game based on the artwork of Piet Mondrian, which gives students the opportunity to develop fluency with the concepts of area and perimeter. The authors share details of the game, including connections and extensions that integrate English language arts and art standards.